2021
DOI: 10.1111/acel.13429
|View full text |Cite
|
Sign up to set email alerts
|

A high‐fat diet exacerbates the Alzheimer's disease pathology in the hippocampus of the AppNL−F/NL−F knock‐in mouse model

Abstract: Insulin resistance and diabetes mellitus are major risk factors for Alzheimer's disease (AD), and studies with transgenic mouse models of AD have provided supportive evidence with some controversies. To overcome potential artifacts derived from transgenes, we used a knock‐in mouse model, AppNL−F/NL−F, which accumulates Aβ plaques from 6 months of age and shows mild cognitive impairment at 18 months of age, without the overproduction of APP. In the present study, 6‐month‐old male AppNL−F/NL−F and wild‐type mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 50 publications
5
32
0
Order By: Relevance
“…We recently demonstrated that type 2 diabetes mellitus (T2DM) induced by a high-fat diet causes an impaired cognitive function in a mild preclinical AD model of App NL-F/NL-F mice accompanied by marked increases in both microgliosis and 8-oxoG accumulation as well as insulin resistance in the hippocampus [ 78 ]. The AD brain exhibits insulin resistance, and T2DM is a major risk factor for AD [ 1 3 , 31 ]; therefore, insulin secretagogues which can induce MUTYH degradation are promising therapeutic agents for the prevention of the AD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that type 2 diabetes mellitus (T2DM) induced by a high-fat diet causes an impaired cognitive function in a mild preclinical AD model of App NL-F/NL-F mice accompanied by marked increases in both microgliosis and 8-oxoG accumulation as well as insulin resistance in the hippocampus [ 78 ]. The AD brain exhibits insulin resistance, and T2DM is a major risk factor for AD [ 1 3 , 31 ]; therefore, insulin secretagogues which can induce MUTYH degradation are promising therapeutic agents for the prevention of the AD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, it was hypothesized that Aβ deposition prior to the onset of HFD consumption may be a prerequisite for exacerbated development or progression of AD-related pathologies in APP knock-in mouse models of AD [ 43 ]. Mazzei et al used the APP NL-F/NL-F knock-in AD mouse model, which expresses APP with a humanized Aβ region under the control of the endogenous APP mouse promoter.…”
Section: Introductionmentioning
confidence: 99%
“…APP NL-F/NL-F knock-in mice start accumulating Aβ as early as at 6 months-of-age and show mild cognitive deficits by 18 months [ 39 ]. APP NL-F/NL-F male mice were fed a 40% HFD or a regular diet starting at 6 months-of-age for 12 consecutive weeks [ 43 ]. The authors found that HFD increases body weight, fasting glucose levels, and glucose tolerance in both APP NL-F/NL-F mice and their WT littermates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations